2001
DOI: 10.1103/physreva.64.012107
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of the probability density in the transient regime for tunneling

Abstract: An exact analytical solution to the time-dependent Schrödinger equation with cutoff wave initial conditions is used to investigate the fast tunneling response of a rectangular potential barrier. We find that just across the tunneling region, the probability density exhibits at short times a transient behavior that may be characterized by a peak t p and a width ⌬t. We show that t p provides the earliest tunneling response of the system and that the top-barrier S-matrix poles play an important role in the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 22 publications
1
78
1
Order By: Relevance
“…The time-dependence in tunnelling has been addressed using various wavepackets by many authors in the past, e.g. [22,23,24,25,26,27]. The distinguishing contribution of the present treatment is the correct many-electron occupation corresponding to finite bias and low temperatures and hence its direct consequences for the current-voltage characteristics.…”
Section: Electronic Transport Through Resonant Tunnelling Bar-rimentioning
confidence: 99%
“…The time-dependence in tunnelling has been addressed using various wavepackets by many authors in the past, e.g. [22,23,24,25,26,27]. The distinguishing contribution of the present treatment is the correct many-electron occupation corresponding to finite bias and low temperatures and hence its direct consequences for the current-voltage characteristics.…”
Section: Electronic Transport Through Resonant Tunnelling Bar-rimentioning
confidence: 99%
“…[6] a cutoff wave initial state has, in addition to tunneling components, momentum components that go above the barrier height. One sees from Eq.…”
Section: Formalismmentioning
confidence: 99%
“…On the theoretical side the above achievements have stimulated work on the issue of time-dependent tunneling. In particular, one finds a number of works that deal with the solution to the time-dependent Schrödinger's equation for cutoff wave initial states [3,4,5,6]. One interesting feature of these approaches is that at asymptotically long times the time-dependent solution goes into the well known stationary solution.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of approaches to this problem [2]. In this paper, an unexpected close relationship is found between a real time Feynman path integral approach [3,4,5] and the quantum shutter approach [6,7], which are, at first sight, unlikely to be related.…”
Section: Introductionmentioning
confidence: 83%
“…Since initially there is no particle along the tunneling region, detecting the particle at the barrier edge at time t should provide a relevant time scale of the tunneling process. In recent work, two of the authors [7,13] analyzed the time evolution of the probability density |Ψ(d, t)| 2 for a rectangular potential barrier using the above formalism. There, it was found that the probability density at the right barrier edge x = d, exhibits at short times a transient structure that they named time-domain resonance.…”
Section: Introductionmentioning
confidence: 99%